Bringing up the Bodies: Material Encounters in Elsa Morante's La Storia. (2nd January 2021) - Walker, Rebecca M.
ABSTRACT: This article addresses Elsa Morante's La Storia (1974) in light of recent developments in critical and feminist theory surrounding the material environment and the body. It analyses the dynamics of material encounters in the novel from several perspectives: it views Rome as a 'misanthropic city' (Thrift 2008) and its bodies, human and otherwise, as fragile; it considers the specificity of female materialities as articulated in the novel; it discusses how discourses of race are articulated spatially; and it explores how the body itself becomes a canvas for the traumas wrought by 'History', as presented in the text. Ultimately, this reading suggests that Morante's positioning and privileging of the materiality of minor subjects, her 'bringing up the bodies', questions received modes of engaging with the past.